Akuntabilitas Pemerintah Desa dalam Pengelolaan Alokasi Dana Desa (ADD) di Desa Manubelon Kecamatan Amfoang Barat Daya Kabupaten Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Villages play a strategic role in governance and development as the frontline of public service delivery. One of the key instruments supporting this role is the Village Fund Allocation (ADD), whose management is required to adhere to the principles of transparency, accountability, and community participation. This study aims to analyze the accountability of the Manubelon Village Government in managing the Village Fund Allocation (ADD) in Manubelon Village, Amfoang Barat Daya District, Kupang Regency. The research employs a descriptive qualitative approach, focusing on five dimensions of accountability: legal and honesty accountability, managerial accountability, program accountability, policy accountability, and financial accountability. Data were collected through observation, in-depth interviews, and documentation, with informants selected using purposive sampling. Data analysis was conducted using the interactive model of Miles and Huberman. The findings indicate that the management of ADD in Manubelon Village has normatively complied with prevailing regulations and involved the community through village deliberation forums. However, several challenges remain in practice, including delays in financial accountability reports, weak administrative discipline among village officials, suboptimal program planning and implementation, and low levels of community participation and understanding of village financial management. Therefore, although accountability in ADD management has been implemented procedurally, its effectiveness still needs to be enhanced through strengthening the capacity of village officials, improving administrative and reporting systems, and optimizing the supervisory roles of the Village Consultative Body (BPD) and the community.